The Effect of Methanolic Extract of Asiatic Bitter Yam (Dioscorea hispida) Tuber on 3rd Instar Larvae Drosophila melanogaster Mortality - Bahri, Syamsul; Wirdullutfi, Wirdullutfi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Drosophila melanogaster is a cosmopolitan insect widely used in genetic studies due to its short life cycle, large offspring numbers, and low cost. One of the plant species known to contain natural pesticides is asiatic bitter yam, which is known by the local name of gadung. Tubers of this species contain dioscorine toxins that have pesticide properties, which can cause nervous disorders. This study aimed to determine the effect of asiatic bitter yam tuber extract (Dioscorea hispida) on 3rd instar larvae of Drosophila melanogaster. The tuber extract was obtained by macerating the sample in 96% alcohol for 72 hours, followed by sieving and then evaporating the extract using a rotatory evaporator. The effect of eight concentrations of tuber extract, namely 0 ppm, 50 ppm, 100 ppm, 150 ppm, 200 ppm, 250 ppm, 300 ppm, and 350 ppm on 3rd instar larvae mortality of this species was studied using a completely randomized design. Every single treatment used 6 larvae with 5 repetitions. The results demonstrated a positive correlation between increasing concentrations of asiatic bitter yam tuber extract and larval mortality rates. One-way ANOVA statistical analysis showed a significant effect of the extract on larval mortality (p < 0.05). Results showed that the asiatic bitter yam tuber extract had a significant effect on 3rd instar larvae Drosophila melanogaster mortality, as the F value was greater than the F critical (10.28571>2.312741). However, the highest percentage of mortality caused by this extract is lower than the value required by the World Food Agency. since the mortality caused by this extract less than 50%, its effect is still below the minimum standard as a pesticide.